2015
DOI: 10.1007/s13277-015-3100-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma +874 T/A polymorphism increases the risk of cervical cancer: evidence from a meta-analysis

Abstract: Data from previous studies about the association between interferon gamma (IFN-γ) +874 T/A (rs2430561) polymorphism and cervical cancer risk offer controversial results. To obtain a more dependable conclusion, this meta-analysis was performed. We selected eight articles including nine case-control studies with 1,116 cases and 1,290 controls, odds ratios (OR) with 95 % confidence intervals (CI) were used to assess the strength of the association. Subgroup analysis was carried out by ethnicity, source of control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
3
13
0
1
Order By: Relevance
“…[51] Moreover, it is still controversial about whether Interferon-γ +874A/T polymorphism could increase the cancer risk. Through a 9 study-based meta-analysis, Sun et al [49] found that IFN-γ +874A/T polymorphism was likely to increase the risk of cervical cancer, while Ge et al [54] concluded that IFN-γ +874A/T polymorphism may not contribute to cancer susceptibility. Hence, well-designed and large-scale studies are demanded.…”
Section: Discussionmentioning
confidence: 99%
“…[51] Moreover, it is still controversial about whether Interferon-γ +874A/T polymorphism could increase the cancer risk. Through a 9 study-based meta-analysis, Sun et al [49] found that IFN-γ +874A/T polymorphism was likely to increase the risk of cervical cancer, while Ge et al [54] concluded that IFN-γ +874A/T polymorphism may not contribute to cancer susceptibility. Hence, well-designed and large-scale studies are demanded.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed the association between IFN-γ +874T/A polymorphism and cervical cancer, 35,36 bladder cancer, 37 liver cancer, 38 and breast cancer, 39 and suggested that T allele might be a protective genotype in cancer for TT genotype produces a high level of IFN-γ. Yet a recent meta-analysis showed no association between IFN-γ +874T/A polymorphism and cancer susceptibility, 40 at the same time, the other meta-analysis found positive association in cervical cancer and breast cancer, 23,26 which suggested that IFN-γ +874T/A polymorphism play different roles in different cancer types; therefore, the conclusion from a pooled analysis for association between IFN-γ +874T/A polymorphism and all cancer types may be unreliable. This meta-analysis confirmed this point.…”
Section: Discussionmentioning
confidence: 99%
“…21 Indeed, our finding is consistent with previous meta-analysis that T allele is a protect genotype among patients in breast cancer, cervical cancer, asthma, and leprosy. 2326 …”
Section: Discussionmentioning
confidence: 99%
“…Whether the uterus would respond similarly to TBBPA or other chemical exposures and engage IFN-dependent pathways is an untested hypothesis. IFN polymorphisms are associated with increased risk of cervical cancer (Sun et al, 2015) but the relationship of IFN-related mechanisms with uterine carcinogenesis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%